Method for producing recycled water-absorbent resin
Patent Information
- Application Number
- JP2023130473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025592000001 
Figure 2025025592000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled water-absorbent resin. [Background technology]
[0002] In recent years, absorbent resins have been widely used as water absorbents in absorbent articles such as paper diapers, sanitary napkins, and incontinence pads, as constituent materials thereof, from the viewpoint of absorbing body fluids. Examples of such absorbent resins include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft polymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and crosslinked products of partially neutralized acrylic acid polymers. Among them, from the viewpoint of water absorption performance, polyacrylic acid (salt)-based absorbent resins using acrylic acid and / or its salt as a monomer are most widely produced industrially, and many technologies related to such absorbent resins have been disclosed.
[0003] Although absorbent articles are generally disposable, interest in recycling absorbent articles is growing due to the rise in environmental awareness. Known technologies for recycling water-absorbing resins used in absorbent articles include a technology in which a superabsorbent polymer derived from used absorbent articles is inactivated, treated with ozone water, then reactivated with an alkaline aqueous solution, and then hydrophilic fine particles are added and dried (Patent Document 1), and a technology in which a used superabsorbent polymer is dehydrated, then a group of superabsorbent polymer particles is attached, and then dried to suppress adhesion between particles and coloring (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. WO2020 / 241025 [Patent Document 2] International Publication No. WO2021 / 205780 Summary of the Invention [Problem to be solved by the invention]
[0005] Currently, various methods for recycling water-absorbent resins from used absorbent articles, etc. have been developed. However, water-absorbent resins recycled by conventional techniques have room for improvement in terms of coloring after long-term storage.
[0006] In the above-mentioned circumstances, one aspect of the present invention is to provide a method for producing a recycled water absorbent resin, which can provide a recycled water absorbent resin that has excellent colorability after long-term storage while maintaining excellent water absorbency. [Means for solving the problem]
[0007] In order to solve the above problems, one embodiment of the present invention includes the following configuration.
[0008] [1] A polymerization step of polymerizing a monomer constituting a water-absorbent resin; and A method for producing a recycled water absorbent resin, comprising a drying step of drying the polymer obtained in the polymerization step, moreover, An addition step (A) of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article or waste generated in the manufacturing process of the water-absorbent resin; and (B) adding a hydroxycarboxylic acid and / or a reducing agent.
[0009] [2] The manufacturing method according to [1], wherein the reducing agent is a sulfur-based reducing agent and / or a phosphorus-based reducing agent.
[0010] [3] The method according to [1] or [2], wherein the reducing agent is an inorganic reducing agent.
[0011] [4] The method according to [3], wherein the inorganic reducing agent is a sulfite and / or a pyrosulfite.
[0012] [5] The method according to any one of [1] to [4], wherein the water-absorbent resin recovered from the used absorbent article or waste generated in the manufacturing process of the water-absorbent resin contains a plurality of types of water-absorbent resins.
[0013] [6] The method according to any one of [1] to [5], wherein the monomer contains p-methoxyphenol in an amount of 200 ppm or less based on the total mass of the monomer.
[0014] [7] The method according to any one of [1] to [6], wherein the monomer contains p-methoxyphenol in an amount of 100 ppm or less based on the total mass of the monomer.
[0015] [8] The method according to any one of [1] to [7], wherein the solubilized polymer contains a decomposing agent for a water-absorbent resin.
[0016] [9] The solubilizing polymer contains an oxidizing agent (A), The method according to any one of [1] to [8], wherein an oxidizing agent (B) is added in the polymerization step.
[0017]
[10] The yellowness index (YI) of the recycled water absorbent resin is 20 or less, The method for producing a recycled water absorbent resin according to any one of [1] to [9], wherein the yellowness index (YI) is a value measured by a method specified in ASTM D1925 in the Hunter Lab color system for the recycled water absorbent resin immediately after production under conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%.
[0018]
[11] The yellowness index (YI) of the recycled water absorbent resin after long-term storage is 25 or less; The method for producing a recycled water absorbent resin according to any one of [1] to
[10] , wherein the yellowness index (YI) after long-term storage is a value measured by a method specified in ASTM D1925 in a Hunter Lab color system for the recycled water absorbent resin stored for 60 days under conditions of room temperature (20°C or higher and 25°C or lower) and a humidity of 50 RH%.
[0019]
[12] The method according to any one of [1] to
[11] , wherein the solubilized polymer contains heavy metal ions in an amount of 10 ppm or less based on the solid content of the solubilized polymer.
[0020]
[13] The method according to any one of [1] to
[12] , wherein the solubilized polymer contains L-ascorbic acid in an amount of 10 ppm or less based on the solid content of the solubilized polymer.
[0021]
[14] The method according to any one of [1] to
[13] , wherein the solubilization rate of the solubilized polymer is 50% by mass or more. Effect of the Invention
[0022] According to one aspect of the present invention, there can be provided a method for producing a recycled water-absorbent resin, which can provide a recycled water-absorbent resin that retains excellent water absorbency and has excellent colorability after long-term storage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] <1. Manufacturing method of recycled water absorbent resin> [1-1] Technical concept of one embodiment of the present invention The present inventors have conducted research on a method for producing a recycled water absorbent resin using, as a part of the raw material, a water absorbent resin recovered from used absorbent articles or a water absorbent resin recovered from waste generated during the manufacturing process of the water absorbent resin or absorbent articles. In the process, the present inventors have found that the hue of the recycled water absorbent resin obtained by the method for producing such a recycled water absorbent resin changes to yellow (becomes yellow) after long-term storage. Such coloring may give consumers an unpleasant impression, such as reminiscent of human waste. Therefore, there is a problem that the water absorbent resin colored to yellow as described above is unsuitable for product use due to its hygienic feel.
[0024] The present inventors speculated that the above-mentioned coloring is due to the presence of residual substances derived from body fluids such as human waste, or residual monomers in the manufacturing process of the water absorbent resin. As a result of intensively studying the above-mentioned problems based on such speculation, the present inventors found that a method for manufacturing a recycled water absorbent resin can be provided by adding a hydroxycarboxylic acid and / or a reducing agent in a manufacturing method for a recycled water absorbent resin, in other words, by including a step of adding a hydroxycarboxylic acid and / or a reducing agent in the manufacturing method for a recycled water absorbent resin, which can provide a recycled water absorbent resin that has excellent colorability after long-term storage while maintaining excellent water absorbency, and thus completed the present invention. Such a recycled water absorbent resin that has excellent colorability after long-term storage while maintaining excellent water absorbency is comparable to a normal (unused) water absorbent resin and can be suitably used for product applications (for example, sanitary material applications).
[0025] [1-2] Manufacturing method of recycled water absorbent resin In one embodiment of the present invention, there is provided a method for producing a recycled water absorbent resin, comprising a polymerization step of polymerizing monomers constituting the water absorbent resin, and a drying step of drying the polymer obtained in the polymerization step, in which a solubilized polymer derived from a water absorbent resin recovered from used absorbent articles or waste generated in the process of producing the water absorbent resin is used as part of a raw material, and further comprising an addition step (B) of adding a hydroxycarboxylic acid and / or a reducing agent. Hereinafter, the "method for producing a recycled water absorbent resin according to one embodiment of the present invention" may be referred to as "this production method".
[0026] According to the present production method, it is possible to provide a recycled water-absorbent resin that has excellent water-absorbency and excellent colorability after long-term storage. The "water-absorbency" and "colorability after long-term storage" of the water-absorbent resin (recycled water-absorbent resin) can be measured or evaluated by the method described in the Examples.
[0027] [1-2-1] Absorbent articles In this specification, the term "absorbent article" refers to an article used for absorbing water. An example of the "absorbent article" is an absorbent article having an absorbent body containing a water-absorbing resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is preferably manufactured by blending the water-absorbing resin with the fibrous material, or by sandwiching the water-absorbing resin between the fibrous material and molding it into a shape such as a film, a tube, or a sheet. Here, the fibrous material may be hydrophilic fiber, such as pulverized wood pulp, cotton linters, crosslinked cellulose fiber, rayon, cotton, wool, acetate, vinylon, etc. Specific examples of the "absorbent article" include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets, but are not limited thereto.
[0028] The term "used absorbent article" in this manufacturing method refers to an absorbent article (particularly, a sanitary material) that has absorbed any liquid (absorbed liquid), particularly bodily fluids such as urine and blood.
[0029] [1-2-2] Water-absorbing resin In this specification, the term "water-absorbent resin" refers to a water-swellable, water-insoluble polymer gelling agent, and generally refers to a conventional water-absorbent resin having a water absorption capacity of 10 to 1000 times its volume. More specifically, it is preferable that the water-absorbent resin before absorbing the liquid to be absorbed satisfies the physical property of CRC of 5 g / g or more as "water-swellable" specified in ERT441.2-02, and satisfies the physical property of Ext (water-soluble content) of 0 to 50 mass% as "water-insoluble" specified in ERT470.2-02.
[0030] Specific examples of water-absorbent resins include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, and cellulose-based resins.
[0031] [1-2-3] Waste generated during the manufacturing process of water-absorbent resin In this specification, the term "waste generated during the manufacturing process of a water-absorbent resin" refers to a water-absorbent resin that is generated during the manufacturing process of a water-absorbent resin and is rejected from product use for some reason (for example, because its water-absorbing properties, color tone, etc. are not within the standard), and is usually discarded, and is therefore referred to as "waste." Examples of "waste generated during the manufacturing process of a water-absorbent resin" include, but are not limited to, fine powder, gel, and water-absorbent resin particles with excessively large or small particle diameters generated during the manufacturing process of a water-absorbent resin.
[0032] [1-2-4] Recycled water-absorbent resin In the present specification, the term "recycled water absorbent resin" refers to a water absorbent resin that uses, as a part of the raw material, a solubilized polymer of a water absorbent resin that contains a liquid to be absorbed, such as human waste, recovered from a used absorbent article, and / or a water absorbent resin that is recovered from waste generated in the manufacturing process of the water absorbent resin. In the present specification, such a water absorbent resin recovered from a used absorbent article or from waste generated in the manufacturing process of the water absorbent resin may be referred to as a "recovered water absorbent resin". In addition, this "recovered water absorbent resin" may include a water absorbent resin contained in an absorbent article that was discarded before use.
[0033] Usually, the recovered water absorbent resin does not have water absorption performance or has very low water absorption performance, and may contain a large amount of impurities derived from body fluids or generated during the manufacturing process of the water absorbent resin. Therefore, the recovered water absorbent resin is not used for product applications for water absorption such as absorbent articles, but is disposed of, thermally recycled as fuel, composted, or otherwise disposed of. On the other hand, the "recycled water absorbent resin" is a water absorbent resin derived from the recovered water absorbent resin, but is obtained by recovering the liquid absorption performance of the recovered water absorbent resin so that it can be used again for water absorption purposes. In other words, the "recycled water absorbent resin" is intended to be a water absorbent resin made from the recovered water absorbent resin as a raw material, has water absorption performance, and can be used for product applications such as absorbent articles.
[0034] [1-2-5] Polymerization process In the polymerization step, a polymer can be obtained by polymerizing the monomers constituting the water absorbent resin. In the polymerization step, as an example, a polymer can be obtained by carrying out a polymerization reaction using an aqueous solution (monomer aqueous solution) containing the monomers constituting the water absorbent resin. In other words, a polymer can be obtained by polymerizing the monomers in the monomer aqueous solution. In this production method, a monomer slurry liquid can be used in addition to the monomer aqueous solution within a range in which the water absorption performance of the obtained water absorbent resin is not reduced, but for the sake of convenience, the case of using a monomer aqueous solution will be described in this section.
[0035] The polymerization step may include a step of preparing an aqueous monomer solution for use in the polymerization step.
[0036] (Preparation of Monomer Aqueous Solution) The aqueous monomer solution is preferably an aqueous solution containing acrylic acid (salt) as a main component.
[0037] The above-mentioned "main component" means that the amount (content) of acrylic acid (salt) used is 50 mol% or more in the total amount (100 mol%) of monomers (in other words, monomers contained in the aqueous monomer solution, excluding the internal crosslinking agent) to be subjected to the polymerization reaction of the water absorbent resin. The content of acrylic acid (salt) in the total amount (100 mol%) of monomers is preferably 70 mol% or more, more preferably 90 mol% or more (upper limit: 100 mol%).
[0038] (acrylic acid) As a monomer serving as a raw material for the water absorbent resin in the present production method, acrylic acid and / or a salt thereof (hereinafter referred to as "acrylic acid (salt)") is used from the viewpoints of the physical properties and productivity of the resulting water absorbent resin.
[0039] The term "acrylate" refers to acrylic acid neutralized with a basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water absorbent resin manufacturing plant.
[0040] (Basic Composition) In the present specification, the term "basic composition" refers to a composition containing a basic compound. More specifically, the basic compound may be an alkali metal carbonate and / or hydrogen carbonate, an alkali metal hydroxide, ammonia, an organic amine, or the like. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, a strongly basic basic compound, for example, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, is preferred, and sodium hydroxide is more preferred.
[0041] (neutralization) In the present production method, it is preferable to neutralize at least a part of the acrylic acid. As the neutralization in the present production method, either neutralization of the acrylic acid (before polymerization) or neutralization of the polymer obtained by polymerizing the acrylic acid (for example, a hydrogel-like crosslinked polymer) (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. In addition, the mode of these neutralizations is not particularly limited, and may be a continuous type or a batch type, but a continuous type is preferable from the viewpoint of production efficiency, etc.
[0042] Regarding the conditions such as the neutralization device, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and U.S. Patent Application Publication No. 2008 / 0194863 may be applied to one embodiment of the present invention.
[0043] The neutralization rate of the monomer (monomer having an acid group including acrylic acid) in this production method is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, further preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% in the total amount of the acid groups of the monomer (100 mol%). By setting the neutralization rate to 10 mol% or more, a water absorbent resin having a sufficient water absorption capacity can be provided, and by setting the neutralization rate to 90 mol% or less, a water absorbent resin having a higher water absorption capacity under pressure can be provided. The neutralization rate of the aqueous monomer solution will be further explained by taking as an example a case where the aqueous monomer solution contains only acrylic acid as a monomer component. In this case, the neutralization rate of the monomer is 75 mol% means that the monomer component contained in the aqueous monomer solution is a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. Such a mixture may be called a partially neutralized product of acrylic acid.
[0044] The above neutralization rate is the same in the case of post-neutralization. The above neutralization rate is also applied to the neutralization rate of the water absorbent resin as a final product. In the present production method, the solubilized polymer of the recovered water absorbent resin is used as a part of the raw material for production of the water absorbent resin, as described later. There is a possibility that the solubilized polymer derived from such a recovered water-absorbing resin contains a basic compound. Therefore, when the solubilized polymer of the recovered water-absorbing resin is used as a part of the raw material for producing a water-absorbing resin, the basic compound contained in the solubilized polymer may neutralize the acrylic acid before polymerization or the polymer after polymerization (for example, the hydrogel-like cross-linked polymer). Therefore, taking into account the neutralization by the basic compound derived from the solubilized polymer, the neutralization (post-neutralization) rate of the monomer in the aqueous monomer solution, the polymer after polymerization, and the water-absorbing resin as the final product is adjusted to a predetermined range.
[0045] (Other monomers) The aqueous monomer solution may contain a monomer (other monomer) other than the acrylic acid (salt). In the present production method, such other monomer can be used in combination with the acrylic acid (salt) to produce a water-absorbing resin.
[0046] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, anionic unsaturated monomers such as (anhydrous) maleic acid, fumaric acid, crotonic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate and / or salts thereof may be suitably used as the other monomer. Moreover, these other monomers may be used alone or in combination of two or more.
[0047] (Internal crosslinking agent) The aqueous monomer solution preferably contains an internal crosslinking agent. As the internal crosslinking agent that can be contained in the aqueous monomer solution, for example, the compounds described in U.S. Patent No. 6,241,928 can be mentioned. Among these, one or more compounds can be used as the internal crosslinking agent in consideration of reactivity.
[0048] When the polymerization step is carried out using an aqueous monomer solution that contains an internal crosslinking agent, the resulting polymer may be internally crosslinked and may therefore also be referred to as a "crosslinked polymer."
[0049] In addition, from the viewpoint of the water absorption performance of the obtained water absorbent resin, the internal crosslinking agent is preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition properties at the drying temperature described below, and further preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit.
[0050] The polymerizable unsaturated group is preferably, for example, an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.
[0051] The amount of the internal crosslinking agent used (content in the aqueous monomer solution) is preferably 0.0001 mol% or more and 10 mol% or less, more preferably 0.001 mol% or more and 1 mol% or less, based on the total amount of the monomer. By setting the amount of the internal crosslinking agent used within the above range, a water-absorbing resin having a desired water-absorbing performance can be obtained. If the amount of the internal crosslinking agent used is less than 0.0001 mol%, the gel strength of the obtained water-absorbing resin tends to decrease and the water-soluble content tends to increase excessively, and if the amount of the internal crosslinking agent used is more than 10 mol%, the water absorption capacity of the obtained water-absorbing resin tends to decrease, which is not preferable. The mol% relative to the total monomer is the percentage of the number of moles of the internal crosslinking agent relative to the total number of moles of the monomer contained in the aqueous monomer solution.
[0052] In the present production method, a method is preferably applied in which a predetermined amount (within the above range) of an internal crosslinking agent is added in advance to the aqueous monomer solution, and the crosslinking reaction is started simultaneously with the polymerization. On the other hand, in addition to the above method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization; a method of radical crosslinking using a radical polymerization initiator; a method of radiation crosslinking using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.
[0053] (Polymerization inhibitor) From the viewpoint of the polymerizability of acrylic acid and the color tone of the water-absorbing resin, the aqueous monomer solution preferably contains a polymerization inhibitor in an amount of 200 ppm or less, more preferably 10 ppm or more and 160 ppm or less, and even more preferably 20 ppm or more and 100 ppm or less. The polymerization inhibitor is not particularly limited, but is preferably a methoxyphenol, more preferably p-methoxyphenol.
[0054] In addition, the recovered water absorbent resin may contain a polymerization inhibitor (e.g., p-methoxyphenol) depending on the manufacturing process of the water absorbent resin from which it is derived. In that case, the solubilized polymer obtained from the recovered water absorbent resin may also contain a polymerization inhibitor (e.g., p-methoxyphenol). In other words, in this manufacturing method, the solubilized polymer described later may contain p-methoxyphenol.
[0055] The aqueous monomer solution according to the present invention may contain impurities derived from each component in the aqueous monomer solution. For example, the description of the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 regarding impurities derived from acrylic acid may be applied to one embodiment of the present invention.
[0056] (Other substances) The aqueous monomer solution may contain substances (other substances) other than the above-mentioned components from the viewpoint of improving the physical properties of the resulting water-absorbing resin.
[0057] Examples of other substances include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts); and other additives such as foaming agents such as carbonates and azo compounds, surfactants, chelating agents, and chain transfer agents.
[0058] When the aqueous monomer solution contains a hydrophilic polymer as an additional substance, the content of the hydrophilic polymer is preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution. When the aqueous monomer solution contains other additives as additional substances, the content of the other additives is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution.
[0059] The above-mentioned other substances may be added to the reaction system after the initiation of polymerization. In this case, it is preferable that the total amount of the other substances contained in the aqueous monomer solution and the other substances added to the reaction system after the initiation of polymerization is within the above-mentioned range.
[0060] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions also fall within the scope of one embodiment of the present invention.
[0061] (Polymerization initiator) In the polymerization step, it is preferable to carry out a polymerization reaction of the monomer using a polymerization initiator. The polymerization initiator used in the polymerization step is appropriately selected depending on the polymerization form and the like, and is not particularly limited. For example, a thermal decomposition type polymerization initiator, a photodecomposition type polymerization initiator, or a redox type polymerization initiator used in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 can be suitably used. In addition, from the viewpoint of handling and the physical properties of the obtained water-absorbing resin, the polymerization initiator is preferably a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate.
[0062] The amount of the polymerization initiator used in the polymerization step is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the total amount of the monomers to be polymerized (monomers contained in the aqueous monomer solution). When a reducing agent is used in combination (i.e., when a redox polymerization initiator is used), the amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the total amount of the monomers. The mol% relative to the monomer refers to the percentage of the number of moles of the polymerization initiator or reducing agent relative to the total number of moles of the monomers contained in the aqueous monomer solution.
[0063] In addition, instead of the above polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or the polymerization reaction may be carried out by using these active energy rays in combination with the polymerization initiator.
[0064] (polymerization form) The polymerization form in the polymerization step is not particularly limited, but from the viewpoint of the water absorption properties of the obtained water absorbent resin and the ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, reversed phase suspension polymerization, more preferably aqueous solution polymerization, reversed phase suspension polymerization, and further preferably aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable. Forms such as continuous belt polymerization and continuous kneader polymerization can also be applied. In addition, a foaming polymerization form in which bubbles (particularly inert gas, etc.) are dispersed in a monomer aqueous solution to carry out polymerization can also be applied.
[0065] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin can be improved.
[0066] The polymerization form may also be acid polymerization. Acid polymerization is a method of obtaining a polymer by polymerizing an acid group-containing monomer including unneutralized acrylic acid and then neutralizing it with a basic composition. A specific embodiment of acid polymerization is disclosed in JP-A-1-103606.
[0067] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.
[0068] In the polymerization step, the polymerization can be carried out under a desired atmosphere, for example, under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, to make the dissolved oxygen less than 1 mg / l).
[0069] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the above-mentioned inert gases or the like) are dispersed in an aqueous monomer solution.
[0070] When the polymerization form in the polymerization step is aqueous solution polymerization, that is, when the monomer is polymerized in an aqueous solution state, the obtained polymer may be in a gel state containing water. Therefore, when such a polymerization form is adopted, the polymer obtained in the polymerization step may be called a "water-containing gel," "gel," "water-containing gel-like polymer," or "gel-like polymer."
[0071] In the polymerization step, an oxidizing agent may be added to the system. In this specification, the oxidizing agent added to the system in the polymerization step is also referred to as oxidizing agent (B) for convenience. The oxidizing agent will be described in detail in the section ([1-2-9] Solubilization step) described later.
[0072] [1-2-6] Drying process This production method includes a drying step in which the polymer (e.g., hydrogel) obtained in the polymerization step is dried. In the drying step, for example, the polymer obtained in the polymerization step is dried to a desired resin solid content to obtain a dried polymer. The resin solid content of the dried polymer is determined from the loss on drying (the change in mass when 1 g of the dried polymer is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.
[0073] The method for drying the polymer is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high-temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0074] The drying temperature (hot air temperature) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of the color tone and drying efficiency of the obtained water-absorbent resin. The drying conditions other than the drying temperature, such as the hot air speed and drying time, can be appropriately set according to the water content and total mass of the polymer to be dried and the target resin solid content. In addition, when band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.
[0075] [1-2-7] Addition step (A) This manufacturing method includes an addition step (A) of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article and / or a solubilized polymer derived from a water-absorbent resin recovered from waste generated in the manufacturing process of the water-absorbent resin, for example, to a reaction system. By adding the solubilized polymer to the reaction system, the solubilized polymer can be used as a part of the raw material. Therefore, in other words, the addition step (A) can be said to be a step of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article or waste generated in the manufacturing process of the water-absorbent resin to the system as a part of the raw material.
[0076] In the actual collection of used absorbent articles, used sanitary materials of various types and manufacturers can be collected without distinction between types and manufacturers. In addition, various manufacturers manufacture various types of water-absorbent resins, and the water-absorbent resins can be collected from waste generated in the manufacturing process of each of these manufacturers without distinction between types and manufacturers. Therefore, the recovered water-absorbent resins may include used water-absorbent resins of various manufacturers and various types. In other words, in this manufacturing method, the water-absorbent resin (recovered water-absorbent resin) may include multiple types of water-absorbent resins.
[0077] In the past, when recycled water absorbent resins containing various manufacturers and various types of water absorbent resins are used as a part of raw materials to obtain recycled water absorbent resins, the water absorption performance of the obtained recycled water absorbent resins may not be stable. However, the method for producing recycled resins according to one embodiment of the present invention has the advantage that recycled water absorbent resins with stable water absorption performance can be obtained even when solubilized polymers derived from recycled water absorbent resins containing various manufacturers and various types of water absorbent resins are used.
[0078] The method of adding the solubilized polymer to the reaction system includes, but is not limited to, adding it as an aqueous solution, adding it as a powder after drying once, and adding it in a slurry state with some undissolved matter remaining. From the viewpoint of the mixability of the solubilized polymer with other components, the adding step (A) is preferably a step of adding the solubilized polymer in the form of an aqueous solution at 30°C or higher. The temperature of the aqueous solution of the solubilized polymer is more preferably 40°C or higher, and even more preferably 50°C or higher.
[0079] In addition, the solubilized polymer may contain a basic compound derived from the recovered water absorbent resin as a raw material. When the solubilized polymer derived from the recovered water absorbent resin contains a basic compound, the neutralization rate of the monomer and / or the water absorbent resin as a final product may change by adding the solubilized polymer to the raw material of the water absorbent resin (e.g., a monomer aqueous solution). Therefore, when the solubilized polymer derived from the recovered water absorbent resin is added to the raw material of the water absorbent resin, it is preferable to adjust the neutralization rate of the monomer and the neutralization rate of the water absorbent resin as a final product to fall within a predetermined range, taking into account the amount of the basic compound contained in the solubilized polymer.
[0080] The solubilizing polymer may contain heavy metal ions, such as Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ The content of heavy metal ions contained in the solubilized polymer is preferably 10 ppm or less, more preferably 5 ppm or less, and even more preferably 1 ppm or less, based on the solid content of the solubilized polymer. If the content of heavy metal ions contained in the solubilized polymer is within the above range, there is an advantage that coloring of the recycled water absorbent resin can be suppressed.
[0081] Furthermore, the solubilized polymer may contain L-ascorbic acid. Examples of L-ascorbic acid include L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl ester of ascorbic acid. The content of L-ascorbic acid contained in the solubilized polymer is preferably 10 ppm or less, more preferably 5 ppm or less, and even more preferably 1 ppm or less, based on the solid content of the solubilized polymer. If the content of heavy metal ions contained in the solubilized polymer is within the above range, there is an advantage that coloring of the recycled water absorbent resin can be suppressed.
[0082] In this manufacturing method, the timing of carrying out the addition step (A), i.e., the timing of adding the solubilizing polymer, is not particularly limited.The addition step (A) is preferably carried out between, for example, the above-mentioned polymerization step and drying step, and any of the steps of the below-mentioned addition step (B), pulverization step, classification step, and surface crosslinking step.In other words, the solubilizing polymer is preferably added into the reaction system between, for example, the above-mentioned polymerization step and drying step, and any of the steps of the below-mentioned addition step (B), pulverization step, classification step, and surface crosslinking step.
[0083] It is preferable that the addition step (A) is carried out during the polymerization step. When the addition step (A) is carried out during the polymerization step, the addition step (A) may be carried out during the preparation step of the aqueous monomer solution. When the addition step (A) is carried out during the preparation step of the aqueous monomer solution, the solubilized polymer may be mixed into the aqueous monomer solution, or the solubilized polymer may be mixed in advance with water and then mixed with other raw materials. Among these, from the viewpoint of uniform mixing of the raw materials, it is preferable to mix the solubilized polymer into the aqueous monomer solution. When the addition step (A) is carried out during the polymerization step, in another embodiment, the solubilized polymer may be added into the reaction system before the start of polymerization, or may be added into the reaction system after the start of polymerization. Among these, it is preferable to add the solubilized polymer into the reaction system before the start of polymerization, from the viewpoint of uniformity of the polymer component.
[0084] When the addition step (A) is carried out during the drying step, the polymer (e.g., a hydrogel) and the solubilizing polymer may be mixed before drying, or the polymer and the solubilizing polymer may be mixed after drying.
[0085] When the addition step (A) is carried out during (simultaneously with) the addition step (B) described below, the solubilized polymer and the hydroxycarboxylic acid and / or the reducing agent may be added together to the reaction system. For example, the solubilized polymer and the hydroxycarboxylic acid and / or the reducing agent may be mixed, and then the resulting mixture may be added to the reaction system.
[0086] When the addition step (A) is carried out during the grinding step described below, the solubilizing polymer may be added to the reaction system before grinding, or may be added to the reaction system during grinding. Furthermore, the solubilizing polymer may be added to the reaction system in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the solubilizing polymer to the reaction system before gel grinding.
[0087] When the addition step (A) is carried out during the classification step described below, the polymer (e.g., the dried polymer) may be mixed with the solubilized polymer before classification, or the polymer may be mixed with the solubilized polymer after classification. From the viewpoint of uniformity of particle size, it is preferable to add the solubilized polymer to the polymer before classification.
[0088] When the addition step (A) is carried out during the surface cross-linking step described later, the water absorbent resin dried in advance may be mixed with the solubilized polymer, or the water absorbent resin surface-cross-linked after surface cross-linking may be mixed with the solubilized polymer. From the viewpoint of uniform mixing of the surface cross-linking liquid and the water absorbent resin, it is preferable to use a powdery solubilized polymer and subject all the surface-cross-linked materials (i.e., particulate dried polymer and powdery solubilized polymer) to surface cross-linking in the form of powder. In addition, when the solubilized polymer is mixed after surface cross-linking, it is preferable to use a solubilized polymer derived from the surface-cross-linked recovered water absorbent resin as the solubilized polymer.
[0089] The solubilized polymer can be obtained by decomposing the recovered water absorbent resin. For example, the method of decomposing the recovered water absorbent resin includes the solubilization step described later. The solubilized polymer may contain a decomposing agent and / or an oxidizing agent used in the process of decomposing the recovered water absorbent resin. The decomposing agent and the oxidizing agent will be described in detail in the section on the solubilization step described later.
[0090] The recovered water-absorbent resin may contain hydroxycarboxylic acids and / or reducing agents, for example, because a metal chelating agent was used during the manufacturing process of the water-absorbent resin prior to use of the recovered water-absorbent resin. As a result, the solubilized polymer derived from the recovered water-absorbent resin may also contain hydroxycarboxylic acids and / or reducing agents.
[0091] The content of the hydroxycarboxylic acid and / or reducing agent contained in the solubilized polymer is not particularly limited, but is preferably 0.01% by mass to 1.0% by mass, more preferably 0.02% by mass to 1.0% by mass, even more preferably 0.02% by mass to 0.5% by mass, and even more preferably 0.02% by mass to 0.4% by mass. When the content of the hydroxycarboxylic acid and / or reducing agent in 100% by mass of the solubilized polymer is 0.01% by mass to 1.0% by mass, it has the advantage of excellent water absorption properties and coloring inhibition.
[0092] The molecular weight of the solubilizing polymer used in the addition step (A) is preferably as low as possible from the viewpoints of the handling property of the solubilizing polymer aqueous solution and the mixability with other raw materials, but is preferably as high as possible from the viewpoints of the balance of the water absorption properties of the water absorbent resin and the reduction of the soluble content, etc. Therefore, from the viewpoints of obtaining a solubilizing polymer with a good balance between the mixability with other raw materials and the water absorption properties and with a reduced soluble content, the mass average molecular weight of the solubilizing polymer is preferably from 30,000 to 1,000,000, more preferably from 30,000 to 800,000, and even more preferably from 40,000 to 600,000.
[0093] The amount of the solubilizing polymer used (addition amount) in the addition step (A) is not particularly limited, but is, for example, preferably 1 mass % or more and 60 mass % or less, more preferably 3 mass % or more and 50 mass % or less, and even more preferably 5 mass % or more and 40 mass % or less, based on the total amount of the recycled water absorbent resin.
[0094] [1-2-8] Addition step (B) The present production method includes an addition step (B) of adding a hydroxycarboxylic acid and / or a reducing agent, for example, to the reaction system. By adding a hydroxycarboxylic acid and / or a reducing agent to the reaction system, colorability after long-term storage can be improved. As a result, the obtained recycled water absorbent resin has an advantage of excellent water absorption performance even without excessive purification.
[0095] In this specification, the term "hydroxycarboxylic acid" refers to a carboxylic acid having a hydroxyl group in the molecule or a salt thereof. Hydroxycarboxylic acids are not particularly limited, but examples thereof include citric acid, malic acid, lactic acid, glyceric acid, and tartaric acid. Among these, citric acid and malic acid are preferred from the viewpoints of water absorption properties and coloring inhibition.
[0096] In this specification, the term "reducing agent" refers to a compound having reducing properties. The reducing agent is not particularly limited as long as it is a compound having reducing properties, but from the viewpoint of water absorption properties and coloring inhibition, it is preferable that the reducing agent is a sulfur-based reducing agent and / or a phosphorus-based reducing agent. In this specification, the term "sulfur-based reducing agent" refers to a "compound having a reducing sulfur atom". In this specification, the term "phosphorus-based reducing agent" refers to a "compound having a reducing phosphorus atom".
[0097] The reducing agent of the present invention may be either an inorganic reducing agent or an organic reducing agent as long as it has reducing properties, but from the viewpoints of water absorption properties and coloring inhibition, it is preferable that it is an inorganic reducing agent. In this specification, the term "inorganic reducing agent" refers to a "reducing inorganic compound."
[0098] Regarding the above sulfur-based reducing agent and / or phosphorus-based reducing agent, generally, the most stable oxidation number of sulfur atom is +6 (positive hexavalent), the most stable oxidation number of phosphorus atom is +5 (positive pentavalent), and each atom with an oxidation number lower than that has reducing property. Therefore, as the sulfur-based reducing agent and / or phosphorus-based reducing agent in the addition step (B), inorganic compounds having reducing sulfur or phosphorus atoms such as +4-valent sulfur compounds (e.g., sulfite, hydrogen sulfite, pyrosulfite), +3-valent sulfur compounds (e.g., dithionite), +2-valent sulfur compounds (e.g., sulfoxylate), +4-valent phosphorus compounds (e.g., hypophosphate), +3-valent phosphorus compounds (e.g., phosphite, pyrophosphite), and +1-valent phosphorus compounds (e.g., hypophosphite) can be used. In the present production method, from the viewpoint of water absorption property and coloring inhibition, the inorganic reducing agent is preferably a sulfite and / or a pyrosulfite.
[0099] Examples of inorganic compounds containing reducing sulfur atoms as sulfur-based reducing agents that can be used in the addition step (B) include, but are not limited to, sulfites such as sodium sulfite, potassium sulfite, calcium sulfite, zinc sulfite, and ammonium sulfite; hydrogen sulfites such as sodium hydrogen sulfite, potassium hydrogen sulfite, calcium hydrogen sulfite, and ammonium hydrogen sulfite; pyrosulfites such as sodium pyrosulfite, potassium pyrosulfite, and ammonium pyrosulfite; dithionites such as sodium dithionite, potassium dithionite, ammonium dithionite, calcium dithionite, and zinc dithionite; trithionites such as potassium trithionate and sodium trithionate; tetrathionites such as potassium tetrathionate and sodium tetrathionate; thiosulfates such as sodium thiosulfate, potassium thiosulfate, and ammonium thiosulfate; nitrites such as sodium nitrite, potassium nitrite, calcium nitrite, and zinc nitrite. Examples of inorganic compounds containing reducing phosphorus atoms as phosphorus-based reducing agents that can be used in the addition step (B) include sodium hypophosphite. Among these, sulfites, hydrogen sulfites, pyrosulfites, and dithionites are preferred because of their high coloring reduction effect, and sodium sulfite, sodium hydrogen sulfite, potassium pyrosulfite, and sodium dithionite are more preferred. As the sulfur-based reducing agent and / or phosphorus-based reducing agent, one of these inorganic compounds containing reducing sulfur atoms and / or inorganic compounds containing reducing phosphorus atoms may be used alone, or two or more of them may be used in combination.
[0100] The organic compound containing a reducing sulfur atom as a sulfur-based reducing agent that can be used in the addition step (B) is not particularly limited, but examples thereof include 2-hydroxy-2-sulfinatoacetic acid sodium formaldehyde sulfoxylate, formamidinesulfinic acid and thioglycolic acid tris(2-carboxyethyl)phosphine hydrochloride (TCEP), tributylphosphine (TBP), etc., and among them, 2-hydroxy-2-sulfinatoacetic acid, 2-hydroxy-2-sulfonatoacetic acid, and / or their salts are preferred. Preferred salts are alkali metal and alkaline earth metal salts, and lithium salts, sodium salts, or potassium salts are preferred, and sodium salts are particularly preferred. 2-hydroxy-2-sulfinatoacetic acid (salt) may be used in combination with 2-hydroxy-2-sulfonatoacetic acid (salt), and may also be used in combination with the inorganic compound described above.
[0101] The amount of the hydroxycarboxylic acid and / or reducing agent added in the addition step (B) is not particularly limited as long as it is an amount that can sufficiently reduce the recovered water absorbent resin, but for example, it is preferably 0.01% by mass or more and 1.0% by mass or less, more preferably 0.02% by mass or more and 1.0% by mass or less, even more preferably 0.02% by mass or more and 0.5% by mass or less, and particularly preferably 0.02% by mass or more and 0.04% by mass or less. If the content of the hydroxycarboxylic acid and / or reducing agent is 0.01% by mass or more, the coloring of the recycled water absorbent resin over time can be suppressed. In addition, if the content of the hydroxycarboxylic acid and / or reducing agent is 1.0% by mass or less, both the effect of suppressing coloring over time and economic efficiency can be achieved.
[0102] In the present production method, it is preferable to add a hydroxycarboxylic acid and / or a reducing agent to the recovered water absorbent resin in the addition step (B) so that the content of the hydroxycarboxylic acid and / or the reducing agent in the obtained recycled water absorbent resin is within the above range. When the addition step (B) is performed after the drying step, the content of the hydroxycarboxylic acid and / or the reducing agent in the recycled water absorbent resin obtained by the present production method is the content of the hydroxycarboxylic acid and / or the reducing agent in the recycled water absorbent resin obtained substantially in the amount of the hydroxycarboxylic acid and / or the reducing agent used in each production step. On the other hand, when the addition step (B) is performed before the drying step, for example, a part of the added hydroxycarboxylic acid and / or the reducing agent may be consumed by volatilization accompanying drying of the recovered water absorbent resin in the drying step, and the content of the hydroxycarboxylic acid and / or the reducing agent in the obtained recycled water absorbent resin may not match the amount of the hydroxycarboxylic acid and / or the reducing agent added in the addition step (B). In this case, the hydroxycarboxylic acid and / or reducing agent can be extracted from the recycled water absorbent resin obtained using water or physiological saline, and appropriately quantified by liquid chromatography, ion chromatography, etc., to measure the content of the hydroxycarboxylic acid and / or reducing agent in the recycled water absorbent resin obtained. For the above reasons, when the addition step (B) is carried out before the drying step, in the addition step (B), in addition to the above-mentioned addition amount, the hydroxycarboxylic acid and / or reducing agent may be added to the recovered water absorbent resin in an amount including the amount of the hydroxycarboxylic acid and / or reducing agent consumed in each step included in the present production method, particularly in the drying step.
[0103] In the addition step (B), the method of adding the hydroxycarboxylic acid and / or the reducing agent to the recovered water absorbent resin may be, for example, a method of adding the hydroxycarboxylic acid and / or the reducing agent as is, a method of adding the hydroxycarboxylic acid and / or the reducing agent in a solution or slurry state, or the like, but is not limited thereto.
[0104] In this production method, the timing of carrying out the addition step (B), i.e., the timing of adding the hydroxycarboxylic acid and / or the reducing agent, is not particularly limited as long as it is after the polymerization step. The addition step (B) is preferably carried out, for example, between the above-mentioned polymerization step, drying step, and addition step (A), and between the below-mentioned pulverization step, classification step, and surface crosslinking step. In other words, the hydroxycarboxylic acid and / or the reducing agent is preferably added to the reaction system, for example, between the above-mentioned polymerization step, drying step, and addition step (A), and between the below-mentioned pulverization step, classification step, and surface crosslinking step.
[0105] From the viewpoint of water absorption properties and coloring suppression, it is preferable that the addition step (B) is performed during the polymerization step. When the addition step (B) is performed during the polymerization step, the addition step (B) may be performed during the preparation step of the aqueous monomer solution. When the addition step (B) is performed during the preparation step of the aqueous monomer solution, the aqueous monomer solution may be mixed with the hydroxycarboxylic acid and / or the reducing agent, or the hydroxycarboxylic acid and / or the reducing agent may be mixed in advance with water and then mixed with other raw materials. When the addition step (A) is performed during the polymerization step, in another embodiment, the hydroxycarboxylic acid and / or the reducing agent may be added to the reaction system before the start of polymerization, or may be added to the reaction system after the start of polymerization. Among these, it is preferable to add the hydroxycarboxylic acid and / or the reducing agent in the preparation step of the aqueous monomer solution from the viewpoint of water absorption properties and coloring suppression.
[0106] [1-2-9] Solubilization step The present production method preferably includes a solubilization step of solubilizing the recovered water absorbent resin to obtain a solubilized polymer. The solubilization step can also be said to be a step of solubilizing the recovered water absorbent resin in water to obtain a solubilized polymer. The solubilized polymer obtained in the solubilization step may be entirely solubilized in water, or may be a partially solubilized product containing a polymer that is not partially solubilized.
[0107] The method for solubilizing the recovered water absorbent resin is not particularly limited as long as it can decompose the recovered water absorbent resin and solubilize it in water. For example, a method for decomposing and solubilizing the recovered water absorbent resin with a decomposing agent (e.g., a reducing agent and a transition metal ion, etc.) (e.g., the method described in JP 2019-131789 A) can be mentioned.
[0108] In the solubilization step, an oxidizing agent may be used as a decomposing agent. That is, in one embodiment of the present invention, the decomposing agent includes an oxidizing agent. Here, the oxidizing agent is a compound having oxidizing properties, which generates radicals by heating. Examples of the oxidizing agent include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. The oxidizing agent may be used alone or in combination of two or more. Of these, hydrogen peroxide is preferably used.
[0109] In the solubilization step, a reducing agent may be used as a decomposing agent. That is, in one embodiment of the present invention, the decomposing agent includes a reducing agent. The reducing agent is a compound having reducing properties, and is a compound that generates radicals when used in combination with the above-mentioned oxidizing agent or the below-mentioned compound that generates transition metal ions. Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amine, ascorbic acid (salt) or its derivatives (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphoric acid esters, and sulfate esters. The oxidizing agent may be used alone or in combination of two or more. Among these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used.
[0110] In the solubilization step, a transition metal ion may be used as a decomposing agent. That is, in one embodiment of the present invention, the decomposing agent contains a transition metal ion. The transition metal ion is, for example, Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ The transition metal ions may be used alone or in combination of two or more. Examples of the compound that generates the transition metal ions include sulfides, such as ferric sulfate. Examples of the compound that generates the transition metal ions include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, sulfates and hydrates thereof, such as ferrous sulfate, etc.
[0111] In the solubilization step, an alkaline compound may be used as a decomposing agent. That is, in one embodiment of the present invention, the decomposing agent includes an alkaline compound. The alkaline compound is a compound that solubilizes the crosslinked portion of the water-absorbing resin by alkaline hydrolysis. Examples of such alkaline compounds include hydroxides of alkaline metals such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; hydroxides of alkaline earth metals such as magnesium hydroxide and calcium hydroxide; ammonia; and amine compounds such as aliphatic amines, alicyclic amines, and aromatic amines. The alkaline compounds may be used alone or in combination of two or more.
[0112] As the decomposition agent in the solubilization step, one of the above-mentioned oxidizing agents, reducing agents, transition metal ions (or compounds that generate transition metal ions) and alkali compounds may be used alone or two or more of them may be used in combination.
[0113] Furthermore, an example of a method using a decomposition agent is a method in which the recovered water absorbent resin is solubilized using ascorbic acid, which is a reducing agent, under conditions of pH 4 to 7.5 (for example, the method described in Japanese Patent No. 3146053).
[0114] When a decomposing agent is used for solubilizing the recovered water-absorbent resin, the obtained solubilized polymer may contain the decomposing agent. In other words, in the present production method, the solubilized polymer may contain a decomposing agent for the water-absorbent resin.
[0115] When an oxidizing agent is used for solubilizing the recovered water absorbent resin, the resulting solubilized polymer may contain the oxidizing agent. In this specification, the oxidizing agent that the solubilizing agent may contain is also referred to as oxidizing agent (A) for convenience. In other words, in this production method, the solubilized polymer may contain oxidizing agent (A).
[0116] In addition, examples of the method for solubilizing the recovered water absorbent resin include a method for solubilizing the recovered water absorbent resin using chlorine dioxide under acidic conditions (e.g., the method described in JP 2019-108639 A), a method for solubilizing the recovered water absorbent resin using hydrogen peroxide (e.g., the method described in JP 2019-108640 A), and a method for solubilizing the recovered water absorbent resin with ozone-containing ozone water (e.g., the method described in JP 2019-085343 A, etc.).
[0117] The solubilized polymer obtained in the solubilization step may be used in the addition step (A) as it is in the form of an aqueous solution (i.e., it may be added to the reaction system), or it may be dried to form a solid and then used in the addition step (A) (i.e., it may be added to the reaction system).
[0118] In this production method, the solubilization rate of the solubilized polymer is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more. This configuration has the advantage of excellent mixability with other raw materials. The solubilization rate of the solubilized polymer can be controlled by adjusting the amount of decomposition agent, decomposition time, decomposition temperature, polymer concentration, etc. In addition, in this specification, the method for measuring the solubilization rate of the solubilized polymer will be described in detail in the following examples.
[0119] [1-2-10] Crushing process The present production method preferably further includes a pulverization step in which the polymer (e.g., hydrous gel) obtained in the polymerization step is pulverized, for example, by a screw extruder such as a kneader or meat chopper, or a pulverizer such as a cutter mill, to obtain a particulate polymer (hereinafter also referred to as a "particulate polymer"). When kneader polymerization is adopted as the polymerization form in the polymerization step, the polymerization step and the pulverization step are carried out simultaneously. In addition, when a particulate polymer (particulate hydrous gel) is directly obtained in the polymerization process, such as in gas phase polymerization or reverse phase suspension polymerization, the pulverization step may not be carried out.
[0120] Regarding the grinding conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.
[0121] [1-2-11] Classification process It is preferable that the present production method further includes a classification step of classifying the polymer obtained in the drying step (also referred to as a "dried polymer") to obtain a particulate polymer having a desired particle size (also referred to as a "particulate dried polymer").
[0122] In the classification step, the method for classifying the dried polymer includes sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)), air flow classification, etc. Among them, from the viewpoint of classification efficiency, sieve classification is preferably selected.
[0123] The particle size of the particulate dry polymer obtained in the classification step is not particularly limited, but for example, the mass average particle size (D50) is preferably 200 μm to 500 μm, more preferably 250 μm to 450 μm, and even more preferably 300 μm to 400 μm. The proportion of particles smaller than 150 μm is preferably less than 5% by mass, more preferably 4% by mass or less, and even more preferably 3% by mass or less.
[0124] In the classification step, the dried polymer may be appropriately pulverized to obtain a particulate dried polymer of a desired particle size. The pulverization method is not particularly limited, and a high-speed rotary pulverizer such as a roll mill, a hammer mill, a screw mill, or a pin mill, a vibration mill, a knuckle type pulverizer, or a cylindrical mixer may be used.
[0125] [1-2-12] Surface crosslinking process The present production method preferably further includes a surface cross-linking step, which is a step of providing a portion with a higher cross-linking density on the surface layer (a portion several tens of μm from the surface of the particulate dry polymer) of the particulate dry polymer obtained through the above-mentioned classification step. The surface cross-linking step is composed of a mixing step, a heat treatment step, and a cooling step (optional).
[0126] In the surface cross-linking step, a surface-cross-linked recycled water absorbent resin is obtained by radical cross-linking on the surface of the particulate dried polymer, surface polymerization, a cross-linking reaction with a surface cross-linking agent, etc. Therefore, the particulate dried polymer to be subjected to the surface cross-linking step can also be said to be a recycled water absorbent resin precursor.
[0127] (Surface cross-linking agent) In the surface crosslinking step, it is preferable to crosslink the surface of the particulate dried polymer using a surface crosslinking agent. The surface crosslinking agent is not particularly limited, but may be an organic or inorganic surface crosslinking agent. Among them, from the viewpoint of the physical properties of the recycled water absorbent resin, the handling of the surface crosslinking agent, and the like, an organic surface crosslinking agent that reacts with a carboxyl group is preferable. Specifically, as the surface crosslinking agent, one or more compounds disclosed in U.S. Patent No. 7,183,456 can be used. More specifically, as the surface crosslinking agent, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or condensates thereof with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, and the like can be used. One of these surface crosslinking agents may be used alone, or two or more may be used in combination. In addition, it is preferable to use these surface crosslinking agents in the state of an aqueous solution (i.e., in the state of a surface crosslinking liquid).
[0128] The amount of the surface crosslinking agent used in the surface crosslinking step (the total amount used when a plurality of agents are used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the particulate dry polymer. The surface crosslinking agent is preferably added in the form of an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the particulate dry polymer. Furthermore, a hydrophilic organic solvent may be used in combination as necessary, and in that case, the amount of the hydrophilic organic solvent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the particulate dry polymer. Each additive added in the "re-wetting step" described later can also be mixed into the aqueous solution of the surface crosslinking agent within the range of 5 parts by mass or less.
[0129] (Mixing process) The surface crosslinking step includes a mixing step of mixing the particulate dry polymer with the above-mentioned surface crosslinking agent. The method of mixing the surface crosslinking agent in the mixing step is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the solution with the particulate dry polymer by preferably spraying or dropping, more preferably spraying, can be mentioned.
[0130] The device for mixing the particulate dry polymer with the surface crosslinking agent is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.
[0131] (Heat treatment process) The surface cross-linking step includes a heat treatment step in which the mixture discharged from the mixing step is heated to cause a cross-linking reaction on the surface of the particulate dry polymer. The heat treatment step can also be called a cross-linking reaction step.
[0132] The apparatus for carrying out the heat treatment is not particularly limited, but preferably includes a paddle dryer. The heating temperature in the heat treatment, in other words, the reaction temperature in the crosslinking reaction, is appropriately set according to the type of the surface crosslinking agent used, but is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less.
[0133] (cooling process) The surface cross-linking step preferably includes a cooling step of cooling the surface-cross-linked particulate dry polymer after the heat treatment.
[0134] In the cooling step, the cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. In addition, the surface crosslinked particulate dry polymer obtained in the heat treatment step is forcibly cooled, if necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less, in the cooling step.
[0135] [1-2-13] Crushing (cutting) process The present manufacturing method may further include a crushing (cutting) step of crushing (cutting) the used absorbent article into crushed (cut) materials.
[0136] In the crushing (cutting) step, the method of crushing (cutting) the used absorbent article is not particularly limited, and examples thereof include a method of cutting using a cutting tool such as a cutter, etc. By carrying out the crushing (cutting) step, it is also possible to facilitate separation of each component such as the water-absorbent resin, pulp, nonwoven fabric, etc. from the used absorbent article in the separation step described below.
[0137] In the present production method, the timing for carrying out the crushing (cutting) step is not particularly limited.
[0138] [1-2-14] Separation process The present manufacturing method may further include a separation step of separating the water-absorbent resin from a used absorbent article. "Separating the water-absorbent resin from a used absorbent article" refers to taking out the water-absorbent resin that has shrunk by discharging the absorbed liquid from gaps in the pulp, nonwoven fabric, etc. contained in the used absorbent article, and dispersing it in a treatment liquid.
[0139] As a method for separating the water-absorbing resin from the used absorbent article, for example, a method of stirring a mixture of the treatment liquid and the used absorbent article can be mentioned. The water-absorbing resin dispersed in the treatment liquid can be recovered by a conventional solid-liquid separation means for separating soluble and insoluble substances, for example, filtration, centrifugation, etc.
[0140] In the present production method, the timing of carrying out the separation step is not particularly limited. The above-mentioned crushing (cutting) step and the separation step can also be carried out in parallel.
[0141] [1-2-15] Other processes In addition to the above-mentioned respective steps, the present production method may include a washing step of washing the recovered water absorbent resin, a dehydration step of dehydrating the recovered water absorbent resin (preferably, the recovered water absorbent resin after the washing step), a sterilization / disinfection step of sterilizing and / or disinfecting the recovered water absorbent resin (preferably, the recovered water absorbent resin after the washing step), and a regeneration step of imparting (regenerating) sufficient water absorption performance (sufficient for product applications) to the recovered water absorbent resin, and the like.
[0142] (Cleaning process) The present manufacturing method preferably includes a washing step of washing the recovered water absorbent resin. The washing step included in the present manufacturing method can be said to be a step of removing impurities (e.g., body fluids such as human waste, impurities generated during the manufacturing process, etc.) present between particles of the swollen gel of the recovered water absorbent resin, on the particle surfaces, etc., by washing with a washing liquid (washing treatment). Specific washing methods for the recovered water absorbent resin include, for example, a method of adding a washing liquid to the recovered water absorbent resin, a method of immersing the recovered water absorbent resin in a washing liquid, a method of stirring the recovered water absorbent resin while immersing it in a washing liquid, etc., but are not limited thereto.
[0143] The washing liquid used in the washing step is not particularly limited as long as it is an aqueous liquid that can wash away impurities and does not alter the recovered water absorbent resin, but it is preferable that the recovered water absorbent resin can absorb the washing liquid and swell because it can remove more impurities, especially impurities inside the recovered water absorbent resin. Examples of such washing liquids include deionized water, tap water, distilled water, physiological saline, seawater, etc. Among the above washing liquids, deionized water, tap water, or distilled water is preferable because of its excellent washing effect.
[0144] The temperature of the cleaning liquid in the cleaning step is not particularly limited, and can be from room temperature to 100° C., or steam of the cleaning liquid can be used. When using a high-temperature cleaning liquid or steam of the cleaning liquid of 60° C. or higher, it is preferable because a sterilizing effect can be expected in addition to the cleaning effect.
[0145] The amount of the washing liquid used in the washing step (total amount used) is not particularly limited as long as the recovered water absorbent resin can be sufficiently washed, but for example, it is preferably 2000 parts by mass or more, more preferably 10000 parts by mass or more, and even more preferably 100000 parts by mass or more, relative to 100 parts by mass of the recovered water absorbent resin.
[0146] When the present production method includes a washing step, the washing step needs to be carried out at least once, but may be carried out multiple times.
[0147] (Dehydration process) The present production method preferably includes a dehydration step of dehydrating the recovered water absorbent resin, preferably the recovered water absorbent resin after the washing step. The dehydration step can also be said to be a step of dehydrating (dehydrating) the recovered water absorbent resin (preferably the swollen gel of the recovered water absorbent resin) to discharge impurities present inside the water absorbent resin together with moisture to the outside of the system.
[0148] In the dehydration step, the method of dehydrating the recovered water absorbent resin is not particularly limited, and is not particularly limited as long as it is a method capable of reducing the moisture content of the swollen recovered water absorbent resin in a state of absorbing liquid (for example, the aqueous liquid used for washing). Specific dehydration methods include, for example, a method of contacting the swollen gel of the recovered water absorbent resin with various dehydrating liquids such as an aqueous solution containing a hydrophilic organic solvent, an aqueous solution with a low pH (for example, 3 or less), and an aqueous solution of a polyvalent metal salt (for example, calcium chloride), as well as a method of applying a voltage to the swollen gel using a pair of electrodes. Methods of contacting the swollen gel of the recovered water absorbent resin with the various dehydrating liquids include, but are not limited to, a method of adding the liquid to the recovered water absorbent resin gel (swollen gel) in a swollen state, a method of immersing the swollen gel in the liquid, and a method of stirring the swollen gel while immersing it in the liquid.
[0149] In the dehydration step, when the swollen gel of the recovered water absorbent resin is immersed in an aqueous solution containing a hydrophilic organic solvent, the concentration of the hydrophilic organic solvent in the aqueous solution in which the recovered water absorbent resin is immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more.
[0150] In this specification, the hydrophilic organic solvent refers to an organic solvent having a solubility of 20 g or more in 100 mL of water at 20° C. As the hydrophilic organic solvent, one having a solubility of 25 g or more in 100 mL of water at 20° C. is more preferable, and one having a solubility of 30 g or more in 100 mL of water at 20° C. is even more preferable.
[0151] Specific examples of such hydrophilic organic solvents include: (1) lower alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, tert-butyl alcohol, etc.; (2) ketones such as acetone, methyl ethyl ketone, etc.; (3) ethers such as tetrahydrofuran, dioxane, etc.; and (4) esters such as methyl acetate, methyl lactate, ethyl lactate, etc. These hydrophilic organic solvents may be used alone or in combination of two or more.
[0152] In the dehydration step, when the swollen gel of the water-absorbent resin is immersed in an aqueous solution with a low pH (for example, 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. As the aqueous solution, an aqueous solution containing an acid can be suitably used. As such an acid, either an inorganic acid or an organic acid can be used. In the case of an inorganic acid, for example, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, for example, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. These acids may be used alone or in combination of two or more.
[0153] In the dehydration step, when the swollen gel of the recovered water absorbent resin is contacted with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include salts of metals such as calcium, magnesium, aluminum, iron, cobalt, nickel, and copper with chlorine, carbon, acetic acid, etc. These polyvalent metal salts may be used alone or in combination of two or more.
[0154] When the present production method includes a dehydration step, the dehydration step may be performed at least once, but may be performed multiple times. When the present production method includes a washing step in addition to the dehydration step, the dehydration step is preferably performed after the washing step.
[0155] The present production method may include at least one of the above-mentioned washing step and dehydration step, or may include both the washing step and the dehydration step. In particular, it is preferable that the present production method includes both the washing step and the dehydration step, since there is an advantage that impurities present inside the swollen gel of the recovered water absorbent resin, between particles, on the particle surfaces, etc. can be more effectively discharged out of the system.
[0156] If the recovered water absorbent resin is obtained after the washing process as shown in the above other process, even if the solubilized polymer obtained from the recovered water absorbent resin is used as a part of the raw material, a recycled water absorbent resin having excellent colorability after long-term storage may be obtained. On the other hand, in the conventional technology, a recycled water absorbent resin having poor colorability after long-term storage is obtained when the recovered water absorbent resin is solubilized without washing or the like and the obtained solubilized polymer is used as a part of the raw material without performing the washing process. However, the manufacturing method according to one embodiment of the present invention has the advantage that a recycled water absorbent resin having excellent colorability after long-term storage can be obtained even if the recovered water absorbent resin is solubilized without washing or the like and the obtained solubilized polymer is used as a part of the raw material.
[0157] [1-2-16] Water absorption properties of recycled water absorbent resin obtained by this manufacturing method The CRC of the recycled water absorbent resin obtained by this manufacturing method is preferably 25g / g or more, more preferably 28g / g or more, more preferably 30g / g or more, even more preferably 34g / g or more, even more preferably 37g / g or more, and particularly preferably 40g / g or more. The CRC of the water absorbent resin (recycled water absorbent resin) being in the above range means that the water absorbent resin (recycled water absorbent resin) has excellent water absorption performance. The CRC of the water absorbent resin (recycled water absorbent resin) can be measured by the method described in the examples.
[0158] "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. Also, "ERT" is an abbreviation for EDANA Recommended Test Methods. In one embodiment of the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original ERT (revised in 2002 / publicly known document).
[0159] The AAP of the recycled water absorbent resin obtained by this manufacturing method is preferably 15 g / g or more, more preferably 20 g / g or more, even more preferably 22 g / g or more, and particularly preferably 24 g / g or more. The AUL of the water absorbent resin (recycled water absorbent resin) being in the above range means that the water absorbent resin (recycled water absorbent resin) has excellent water absorption performance. The AUL of the water absorbent resin (recycled water absorbent resin) can be measured by the method described in the examples.
[0160] The yellowness index (YI) of the recycled water absorbent resin obtained by the present production method is preferably 30 or less, more preferably 25 g / g or less, and particularly preferably 20 g / g or less. The yellowness index (YI) of the water absorbent resin (recycled water absorbent resin) being in the above range means that the water absorbent resin (recycled water absorbent resin) has excellent colorability (in other words, it is a water absorbent resin with suppressed coloration). The yellowness index of the water absorbent resin (recycled water absorbent resin) can be measured by the method described in the Examples.
[0161] The yellowness index (YI) of the recycled water absorbent resin obtained by the present production method after long-term storage is preferably 30 or less, more preferably 25 g / g or less, and particularly preferably 20 g / g or less. The yellowness index (YI) of the water absorbent resin (recycled water absorbent resin) in the above range means that the water absorbent resin (recycled water absorbent resin) has excellent colorability even after long-term storage. The yellowness index of the water absorbent resin (recycled water absorbent resin) after long-term storage can be measured by the method described in the Examples.
[0162] The residual monomer amount of the recycled water absorbent resin obtained by this manufacturing method is preferably 500 ppm or less, more preferably 300 ppm or less, even more preferably 200 ppm or less, and particularly preferably 100 ppm or less. The residual monomer amount of the water absorbent resin (recycled water absorbent resin) being within the above range means that the water absorbent resin (recycled water absorbent resin) is excellent in safety to the human body. The residual monomer amount of the water absorbent resin (recycled water absorbent resin) can be measured by the method described in the examples.
[0163] The amount of residual acrylamide in the recycled water absorbent resin obtained by the present production method is preferably below the detection limit (less than 0.1 ppm). This is because acrylamide is a highly toxic and hazardous substance classified as carcinogenicity category 1. The amount of residual acrylamide in the water absorbent resin (recycled water absorbent resin) can be measured by the method described in the Examples.
[0164] [1-2-17] Other In this specification, unless otherwise specified, "ppm" means "ppm by mass."
[0165] In this specification, "acid (salt)" means "acid and / or its salt." "(Meth)acrylic" means "acrylic and / or methacrylic."
[0166] In this specification, the unit of volume "liter" may be written as "l" or "L". EXAMPLES
[0167] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.
[0168] (Measurement and evaluation methods) The methods for measuring and evaluating each physical property in the examples and comparative examples are as follows.
[0169] (a) CRC The "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure with respect to a 0.90% by mass aqueous solution of sodium chloride. The specific method for measuring the CRC of a water-absorbent resin (recycled water-absorbent resin) was as follows.
[0170] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the obtained values of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (1): CRC of absorbent resin (g / g) = (W1-W0) / (mass of absorbent resin)-1···Equation (1).
[0171] (b) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.
[0172] The AAP0.3 of the above water-absorbent resin (recycled water-absorbent resin) was measured in accordance with ERT442.2-02. Specifically, 0.9 g of the water-absorbent resin was placed in a large excess of 0.9% by mass aqueous sodium chloride solution for 1 hour, and the AAP0.3 was measured at 2.07 kPa (21 g / cm 2 The value was measured after swelling under a pressure of 0.5 psi (0.3 psi).
[0173] (c) Solids concentration of the solubilized polymer aqueous solution In this specification, the solids concentration of the solubilized polymer aqueous solution was measured by the following method. That is, a solubilized polymer aqueous solution with a mass Wa (g) was placed on an aluminum dish with a mass Wb (g) and dried in a hot air circulating oven at 180°C for 3 hours. Thereafter, the total mass Wc (g) of the solubilized polymer and the aluminum dish was measured. The solids concentration of the solubilized polymer aqueous solution was calculated from the obtained values of Wa, Wb, and Wc according to the following formula (2): Solids concentration of solubilized polymer aqueous solution (mass%) = {(Wc - Wb) / Wa} × 100 Equation (2).
[0174] (d) Color evaluation (initial YI value / yellowness) The coloring evaluation of the water-absorbent resin was performed using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). An accessory 35Φ×15H round cell, a 35Φ×15H cell case, and a standard white board for powder were used. About 1.5 g of the water-absorbent resin immediately after production was uniformly filled on the sample stage so that there was no gap on the bottom surface. Under the conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%, the YI value (yellowness index; Yellow Index, ASTM D1925) in the Hunter Lab color system of the water-absorbent resin immediately after production (recycled water-absorbent resin) was measured from the back side of the sample stage using the spectrophotometer, and the initial YI value of the water-absorbent resin was determined.
[0175] (e) Coloration evaluation after long-term storage (YI value / yellowness after 60 days) The YI value (yellowness index; ASTM D1925) was measured by the same method as in the above-mentioned (c) Coloring evaluation, except that the YI value was measured after storing the water absorbent resin for 60 days under the conditions of room temperature (20° C. or higher and 25° C. or lower) and humidity of 50 RH%, and this was regarded as the YI value of the water absorbent resin after long-term storage.
[0176] In addition, the lower the YI value of the water-absorbent resin, the less colored the water-absorbent resin is, and the closer it is to white, the less colored the water-absorbent resin is. On the other hand, the higher the YI value of the water-absorbent resin, the more colored the water-absorbent resin is, and the closer it is to yellow, the less colorable the water-absorbent resin is.
[0177] (f) Residual Monomer Amount 200 ml of 0.9% by mass sodium chloride aqueous solution was weighed out into a plastic container with a capacity of 250 ml and a lid. Next, 1.00 g of water absorbent resin was added to the sodium chloride aqueous solution, and then the mixture was stirred at 500 rpm for 1 hour using a 35 mm stirrer tip. By this operation, the remaining monomer in the water absorbent resin was extracted.
[0178] Subsequently, the extract was filtered through a filter (0.45 μm), and the obtained filtrate was analyzed by high performance liquid chromatography (HPLC) to quantitatively determine the amount of remaining monomer in the water absorbent resin.
[0179] (g) Residual acrylamide content 200 ml of 0.9% by mass sodium chloride aqueous solution was weighed out into a 250 ml plastic container with a lid. Next, 1.00 g of water-absorbent resin was added to the sodium chloride aqueous solution, and the mixture was stirred at 500 rpm for 1 hour using a 35 mm stirrer tip. By this operation, the remaining acrylamide in the water-absorbent resin was extracted.
[0180] Subsequently, the extract was filtered through a filter (0.45 μm), and the obtained filtrate was analyzed by high performance liquid chromatography (HPLC) to quantitatively determine the amount of acrylamide remaining in the water-absorbent resin.
[0181] (h) Urea content 200.0 g of 0.9% by mass sodium chloride aqueous solution was weighed out into a plastic container with a capacity of 250 ml and a lid. Next, 1.00 g of water-absorbent resin was added to the sodium chloride aqueous solution, and the mixture was stirred for 16 hours by rotating a stirrer. By this operation, the urea content in the water-absorbent resin was extracted.
[0182] Subsequently, the extract was filtered through a filter (0.45 μm), and the obtained filtrate was analyzed by liquid chromatography (HPLC) to quantitatively determine the amount of urea contained in the water-absorbent resin.
[0183] (i) Calcium and magnesium contents After adding nitric acid to the water-absorbent resin, the resin was decomposed by stepwise heating and microwave irradiation. The amounts of calcium and magnesium contained in the resin were quantified by ICP emission spectroscopy.
[0184] (j) Urine tolerance evaluation 20.0 g of physiological saline (at 37°C, assuming body temperature) containing 1.00 g of recycled water absorbent resin and 0.05% by mass of L-ascorbic acid was added to a sealed container with a capacity of 200 ml, and the container was sealed and allowed to swell 20 times. After 16 hours, the container was tilted 90° to check the state (fluidity) of the gel. If the gel had no fluidity, the urine resistance was rated as "+ (good)", if the gel had fluidity, the urine resistance was rated as "- (slightly poor)", and if the gel was in solution, the urine resistance was rated as "-- (poor)". The criteria for urine resistance evaluation are shown in Table 1.
[0185] [Table 1]
[0186] In the urine resistance evaluation, a fluidity of pass (+) level or higher indicates that the recycled water absorbent resin being evaluated is a recycled water absorbent resin having excellent water absorption properties.
[0187] [Production Example 1] A reaction solution was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight 523) in 550 parts by mass of an aqueous solution of 38% by mass of sodium acrylate (neutralization rate 71 mol%; 200 ppm of p-methoxyphenol was added as a polymerization inhibitor relative to sodium acrylate). The reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere.
[0188] The reaction liquid was then fed to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the gas in the system was replaced with nitrogen gas while maintaining the liquid temperature at 30°C. Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the system while stirring the liquid in the kneader, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30°C or higher and 95°C or lower. After 60 minutes had elapsed since the start of polymerization, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out of the system.
[0189] The obtained hydrogel was dried with hot air at 150° C. for 100 minutes. The dried product was then pulverized using a vibration mill. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm. By this operation, an irregularly pulverized water absorbent resin precursor (S1) was obtained.
[0190] A surface crosslinking agent composition liquid consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water was added to 100 parts by mass of the obtained water absorbent resin precursor (S1), and the obtained mixture was mixed. Next, the obtained mixture was heat-treated at 100°C for 45 minutes to perform surface crosslinking of the water absorbent resin precursor (S1), thereby obtaining a water absorbent resin (S1).
[0191] The obtained water absorbent resin (S1) had a mass average particle size of 400 μm, a water soluble component amount of 9 mass %, a CRC of 41.7 g / g, an AAP0.3 of 30.7 g / g, and a white color tone.
[0192] Next, 20.0 g of the water absorbent resin (S1) was placed in a beaker, and 600.0 g of artificial urine (a solution consisting of 1.9 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, and 97.1 mass% ion-exchanged water) was added to the beaker. After that, the beaker was left at room temperature for 24 hours, and the obtained product was used as a simulated used water absorbent resin (1).
[0193] [Production Example 2] Into a beaker, 620 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 1800.0 g of ion-exchanged water were added and stirred for 15 minutes (washing process (first water washing treatment)). Then, the contents of the beaker were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh.
[0194] 1942.5 g of the filtrate obtained by the filtration after the water washing treatment was returned to an empty beaker, and 1900.0 g of acetone was added to the beaker and stirred for 15 minutes (dehydration treatment).Then, the content of the beaker was filtered through a 100 mesh stainless steel wire mesh.
[0195] Subsequently, 104.2 g of the filtrate after the dehydration treatment obtained by the filtration was returned to an empty beaker, 100 g of deionized water was added, and the mixture was heated to 80° C. while stirring, and 3.0 g of a 30% by mass aqueous hydrogen peroxide solution was added to the system. This operation started decomposition (solubilization) of the simulated used water absorbent resin (1). After 4 hours had elapsed since the start of decomposition, the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh. This operation obtained an aqueous solution of solubilized polymer (1) that solubilized the simulated used water absorbent resin (1) as a filtrate. The mass average molecular weight of the solubilized polymer (1) was 108,000, the urea content was 1.5% by mass, and the Ca content and Mg content were 0.03% by mass.
[0196] In addition, the insoluble matter (filtrate) remaining on the wire net after the filtration was thoroughly washed with ion-exchanged water, and then the insoluble matter together with the wire net was dried for 2 hours in an oven at 180° C. Thereafter, the solubilization rate of the water absorbent resin was calculated according to the following formula (4), and was found to be 99.7%.
[0197] Solubilization rate (%) of water-absorbent resin = [1 - {(mass of wire mesh and insoluble matter after drying) - (mass of wire mesh)} / (mass of water-absorbent resin before decomposition)] × 100 Equation (4).
[0198] The aqueous solution of solubilized polymer (1) was then concentrated using an evaporator to obtain a solubilized polymer concentrate (1) having a solid content of 21.1% by mass.
[0199] [Production Example 3] In a beaker, 620 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 400.0 g of ion-exchanged water were added and stirred (washing step (first water washing treatment)). The temperature was raised to 80° C. while stirring, and 3.0 g of a 30% by mass aqueous hydrogen peroxide solution was added to the system. This operation started decomposition of the simulated used water absorbent resin (1). After 4 hours had elapsed since the start of decomposition, the contents of the beaker were filtered through a 100-mesh stainless steel wire screen. This operation gave an aqueous solution of a solubilized polymer (2) that had solubilized the simulated used water absorbent resin (1) as a filtrate. The mass-average molecular weight of the solubilized polymer (2) was 101,000, the urea content was 28.8% by mass, and the Ca content and Mg content were 0.94% by mass.
[0200] Furthermore, the solubilization rate of the water-absorbent resin was determined by the same procedure as in Production Example 2, and was found to be 99.4%.
[0201] The aqueous solution of solubilized polymer (2) was then concentrated using an evaporator to obtain a solubilized polymer concentrate (2) having a solid content of 21.2% by mass.
[0202] [Comparative Example 1] (Polymerization process) 0.42 parts by mass of polyethylene glycol diacrylate (molecular weight 523) was dissolved in 522.5 parts by mass of 38% by mass aqueous solution of sodium acrylate (neutralization rate 71 mol%) to obtain a reaction solution (C1) (aqueous monomer solution) (aqueous monomer solution preparation step). The reaction solution (C1) was degassed for 30 minutes under a nitrogen gas atmosphere.
[0203] Next, the reaction liquid (C1) and 50.0 parts by mass of the solubilized polymer concentrate (1) obtained in Production Example 2 were added to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid (addition step (A)), and the gas in the system was replaced with nitrogen gas while maintaining the liquid temperature at 30°C.
[0204] Next, while stirring the liquid in the kneader, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the system, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30°C or higher and 95°C or lower. After 60 minutes had passed since the start of the polymerization, the hydrogel (C1) was taken out of the system.
[0205] In Comparative Example 1, the addition step (A) was carried out during the polymerization step.
[0206] (drying process) The resulting hydrogel (C1) was dried with hot air at 170° C. for 30 minutes.
[0207] (Classification process) Thereafter, the dried product was pulverized using a vibration mill. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm. Through this operation, a recycled water absorbent resin (C1) in an irregularly pulverized state was obtained.
[0208] The recycled water absorbent resin (C1) thus obtained was not colored and had a white color. The physical properties of the recycled water absorbent resin (C1) are shown in Table 2.
[0209] [Example 1] In Comparative Example 1, after the initiation of polymerization, 1000 ppm of trisodium diethylenetriaminepentaacetate as a chelating agent and 1500 ppm of DL-malic acid as a hydroxycarboxylic acid were added relative to the monomer solid content (mass), and the mixture was dried with hot air at 150°C for 100 minutes. The same operations as in Comparative Example 1 were carried out to obtain a recycled water absorbent resin (1) in an irregularly crushed form. That is, in Example 1, the addition step (B) was carried out during the polymerization step. The obtained recycled water absorbent resin (1) was not colored and had a white color tone. The physical properties of the recycled water absorbent resin (1) are shown in Table 2.
[0210] [Comparative Example 2] In Comparative Example 1, the solubilized polymer concentrate (1) was replaced with the solubilized polymer concentrate (2) obtained in Production Example 3, and the same operation as in Comparative Example 1 was performed to obtain a recycled water absorbent resin (C2) in an irregularly crushed form. The obtained recycled water absorbent resin (C2) was pale yellow. The physical properties of the recycled water absorbent resin (C2) are shown in Table 2.
[0211] [Example 2] In Comparative Example 2, after the start of polymerization, 1000 ppm of trisodium diethylenetriaminepentaacetate as a chelating agent and 1500 ppm of DL-malic acid as a hydroxycarboxylic acid were added relative to the monomer solid content (mass), and the mixture was dried with hot air at 150°C for 100 minutes. The same operations as in Comparative Example 2 were carried out to obtain a recycled water absorbent resin (2) in an irregularly crushed form. That is, in Example 2, the addition step (B) was carried out during the polymerization step. The obtained recycled water absorbent resin (2) was pale yellow in color. The physical properties of the recycled water absorbent resin (2) are shown in Table 2.
[0212] [Comparative Example 3] The same operation as in Comparative Example 1 was performed except that the solubilized polymer concentrate (1) was not added, to obtain a recycled water absorbent resin (C3) in an irregularly crushed form. The obtained recycled water absorbent resin (C3) was not colored and had a white color. The physical properties of the recycled water absorbent resin (C3) are shown in Table 2.
[0213] [Comparative Example 4] The same operation as in Comparative Example 2 was carried out except that 3% by mass (based on the solid content of the water absorbent resin) of hydrogen peroxide was added as a bleaching agent to the obtained hydrogel in Comparative Example 2, to obtain a recycled water absorbent resin (C4) in an irregularly crushed form. The physical properties of the obtained recycled water absorbent resin (C4) are shown in Table 2.
[0214] [Example 3] (Polymerization process) A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 103.7 g of a 48.5 mass % aqueous sodium hydroxide solution, and 389.0 g of deionized water, and mixed to prepare an aqueous monomer solution (3').
[0215] Next, the solubilized polymer concentrate (1) obtained in Production Example 2 was added to the monomer aqueous solution (3') in an amount of 5% by mass based on the monomer solid content (addition step (A)), and the solution was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare the monomer aqueous solution (3) (monomer aqueous solution preparation step). At this time, the temperature of the monomer aqueous solution (3) rose to 77.9°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to become a transparent homogeneous solution.
[0216] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (3), and the mixture was immediately poured into a stainless steel vat-type container (bottom surface 340 mm×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to the pouring of the aqueous solution of monomer (3) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40° C. after the aqueous solution of monomer (3) was poured into the vat-type container. The polymerization reaction started 70 seconds after the aqueous solution of monomer (3) was poured into the vat-type container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating water vapor. After the reaction, the reactants shrunk to a size slightly larger than the vat-type container. The reactants were taken out as a hydrous gel (3) 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0217] In Example 3, the addition step (A) was carried out during the polymerization step.
[0218] (Crushing process) The hydrogel (3) obtained by the polymerization reaction was cut into strips.
[0219] As a reducing agent, a 10% by mass aqueous solution of sodium sulfite was added in an amount of 1000 ppm relative to the monomer solid content (addition step (B)), and after mixing, the gel was crushed with a meat chopper having a die diameter of 7.5 mm.
[0220] (drying process) The crushed hydrogel (3) was spread on a wire net with a mesh size of 50 mesh (opening size of 300 μm) and dried with hot air at 190° C. for 60 minutes.
[0221] (Classification process) Next, the dried product was further pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized recycled water absorbent resin (3). The physical properties of the obtained recycled water absorbent resin (3) are shown in Table 2.
[0222] [Comparative Example 5] The same operation as in Example 3 was performed except that the 10 mass% sodium sulfite aqueous solution was not added, to obtain an irregularly crushed recycled water absorbent resin (C5). The physical properties of the obtained recycled water absorbent resin (C5) are shown in Table 2.
[0223] [Table 2]
[0224] (summary) From Table 2, it can be seen that the recycled water absorbent resins of Examples 1 to 3 in which the addition step (B) was carried out exhibit excellent colorability (particularly colorability after long-term storage) and urine resistance, compared with the recycled water absorbent resins of Comparative Examples 1 to 5 in which the addition step (B) was not carried out (i.e., no hydroxycarboxylic acid and / or reducing agent was added).
[0225] These results show that by adding a hydroxycarboxylic acid and / or a reducing agent at an appropriate timing during the manufacturing process, it is possible to provide a recycled water-absorbent resin that retains excellent water absorbency and has excellent colorability even after long-term storage. [Industrial Applicability]
[0226] According to one aspect of the present invention, a recycled water-absorbent resin that suppresses odors generated when unused and when absorbing water can be provided. The recycled water-absorbent resin can be suitably used for various applications, particularly for sanitary products such as paper diapers, sanitary napkins, and adult incontinence products.
Claims
1. A polymerization step of polymerizing a monomer constituting the water absorbent resin; and A method for producing a recycled water absorbent resin, comprising a drying step of drying the polymer obtained in the polymerization step, moreover, An addition step (A) of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article or waste generated in the manufacturing process of the water-absorbent resin; and (B) adding a hydroxycarboxylic acid and / or a reducing agent.
2. The method according to claim 1 , wherein the reducing agent is a sulfur-based reducing agent and / or a phosphorus-based reducing agent.
3. The method according to claim 1 , wherein the reducing agent is an inorganic reducing agent.
4. The method according to claim 3, wherein the inorganic reducing agent is a sulfite and / or a pyrosulfite.
5. The method according to claim 1 , wherein the water-absorbent resin recovered from the used absorbent article or waste generated in the process of producing the water-absorbent resin contains a plurality of types of water-absorbent resin.
6. The method according to claim 1, wherein the monomer contains 200 ppm or less of p-methoxyphenol based on the total weight of the monomer.
7. The method according to claim 1, wherein the monomer contains p-methoxyphenol in an amount of 100 ppm or less based on the total weight of the monomer.
8. The method according to claim 1 , wherein the solubilizing polymer comprises a decomposing agent for a water-absorbent resin.
9. the solubilizing polymer comprises an oxidizing agent (A); The method according to claim 1 , wherein an oxidizing agent (B) is added in the polymerization step.
10. The yellowness index (YI) of the recycled water absorbent resin is 20 or less, The method for producing the recycled water absorbent resin according to claim 1, wherein the yellowness index (YI) is a value measured by a method specified in ASTM D1925 in the Hunter Lab color system for the recycled water absorbent resin immediately after production under conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%.
11. The yellowness index (YI) of the recycled water absorbent resin after long-term storage is 25 or less, The method for producing a recycled water absorbent resin according to claim 1, wherein the yellowness index (YI) after the long-term storage is a value measured by a method specified in ASTM D1925 in a Hunter Lab color system for the recycled water absorbent resin stored for 60 days under conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%.
12. The method according to claim 1 , wherein the solubilized polymer contains heavy metal ions in an amount of 10 ppm or less based on the solid content of the solubilized polymer.
13. The method according to claim 1, wherein the solubilizing polymer contains L-ascorbic acid in an amount of 10 ppm or less based on the solid content of the solubilizing polymer.
14. The method according to claim 1 , wherein the solubilization rate of the solubilizing polymer is 50% by mass or more.
Citation Information
Patent Citations
Method for recycling superabsorbent polymer derived from used absorbent article and recycled superabsorbent polymer derived from used absorbent article
WO2020241025A1
Method for producing highly water-absorbing recycled polymer, and highly water-absorbing recycled polymer
WO2021205780A1